Cerebral foreign body reaction after carotid aneurysm stenting. Issue 1 (February 2016) - Lorentzen, Anastasia Orlova; Nome, Terje; Bakke, Søren Jacob; Scheie, David; Stenset, Vidar; Aamodt, Anne Hege
Flow diverter stents are new important tools in the treatment of large, giant, or wide-necked aneurysms. Their delivery and positioning may be difficult due to vessel tortuosity. Common adverse events include intracranial hemorrhage and ischemic stroke, which usually occurs within the same day, or the next few days after the procedure. We present a case where we encountered an unusual intracerebral complication several months after endovascular treatment of a large left internal carotid artery aneurysm, and where brain biopsy revealed foreign body reaction to hydrophilic polymer fragments distally to the stent site. Although previously described, embolization of polymer material from intravascular equipment is rare. We could not identify any other biopsy verified case in the literature, with this particular presentation of intracerebral polymer embolization – a multifocal inflammation spread out through the white matter of one hemisphere without hemorrhage or ischemic changes.